2007
DOI: 10.1007/s00424-007-0279-2
|View full text |Cite
|
Sign up to set email alerts
|

Nonselective cation channels are essential for maintaining intracellular Ca2+ levels and spontaneous firing activity in the midbrain dopamine neurons

Abstract: Intracellular Ca2+ and Ca2+-permeable ion channels are important in regulating the firing activity and pattern of midbrain dopamine neurons, but the role of Ca2+-permeable nonselective cation channels (NSCCs) on spontaneous firing activity is unclear. Therefore, we investigated how Ca2+-permeable NSCCs modulate spontaneous firing activity and cytosolic Ca2+ concentration ([Ca2+]c) in acutely isolated midbrain dopamine neurons of the rat. Applications of voltage-dependent Ca2+ channels antagonists failed to abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 56 publications
3
35
1
Order By: Relevance
“…Although application of dihydropyridines significantly reduced the intensity of burst firing in SN DA neurons, we observed a less consistent effect of Ca v 1 channel blockade on autonomous activity than some (Nedergaard et al, 1993; Mercuri et al, 1994) but not all studies (Fujimura and Matsuda, 1989; Shepard and Stump, 1999; Kim et al, 2007; Puopolo et al, 2007) have reported. After 10–15 minute dihydropyridine application the frequency of autonomous activity decreased in 8 neurons and increased in 8 neurons and the regularity of firing decreased in 11 neurons and increased in 5 neurons.…”
Section: Resultscontrasting
confidence: 83%
See 3 more Smart Citations
“…Although application of dihydropyridines significantly reduced the intensity of burst firing in SN DA neurons, we observed a less consistent effect of Ca v 1 channel blockade on autonomous activity than some (Nedergaard et al, 1993; Mercuri et al, 1994) but not all studies (Fujimura and Matsuda, 1989; Shepard and Stump, 1999; Kim et al, 2007; Puopolo et al, 2007) have reported. After 10–15 minute dihydropyridine application the frequency of autonomous activity decreased in 8 neurons and increased in 8 neurons and the regularity of firing decreased in 11 neurons and increased in 5 neurons.…”
Section: Resultscontrasting
confidence: 83%
“…In concordance with some studies (Fujimura and Matsuda, 1989; Shepard and Stump, 1999; Kim et al, 2007; Puopolo et al, 2007) but not all studies (Nedergaard et al, 1993; Mercuri et al, 1994) but not all studies (Nedergaard et al, 1993; Mercuri et al, 1994) the effects of Ca v 1 channel blockade on spontaneous/autonomous activity were variable. Indeed, it is becoming increasingly clear that a variety of channels contribute to autonomous firing in these neurons including Na v , Ca v 2.1, HCN and non-selective cation channels (Grace and Onn, 1989; Neuhoff et al, 2002; Chan et al, 2007; Kim et al, 2007; Puopolo et al, 2007; Guzman et al, 2009).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…One interpretation of these results is that the dendrites or axon initial segment (AIS), which are sheared off during acute isolation, contribute to pacemaking, rendering it sensitive to antagonism of L-type Ca 2+ channels. Underscoring the importance of these regions to the pacemaking process, SNc DA neurons in tissue slices also were insensitive to TRP channel antagonists 2-APB (20 μM, n=4, p>0.05) and SKF 96365 (20 μM, n=4, p>0.05), in contrast to the situation reported in acutely isolated DA neurons (Kim et al, 2007). …”
Section: Resultsmentioning
confidence: 84%